2016
DOI: 10.1080/2159256x.2016.1176634
|View full text |Cite
|
Sign up to set email alerts
|

TE-domestication and horizontal transfer in a putative Nef-AP1mu mimic of HLA-A cytoplasmic domain re-trafficking

Abstract: Genes of the major histocompatibility complex (MHC; also called HLA in human) are polymorphic elements in the genomes of sharks to humans. Class-I and class-II MHC loci appear responsible for much of the genetic linkage to myriad disease states via the capacity to bind short (~8-15 a.a.) peptides of a given pathogen's proteome, or in some cases, the altered proteomes of cancerous cells, and even (in autoimmunity) certain nominal 'self' peptides (Janeway, 2004).1 Unfortunately, little is known about how the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, when talking about one “gene”, we do not refer to only one sequence. One gene could have different transcription start/termination sites (Soong et al 1994 ), translation start/termination sites (Kochetov et al 2005 ), alternative splicing patterns (Liu et al 2015 ), nucleotide modifications (Chandola et al 2015 ), protein modifications (Fung and Liu 2018 ), and even the switch between coding and non-coding genes, termed domestication (Murray and Murray 2016 ). All these factors and their combinations result in the endless isoforms of transcripts and protein sequences, even they are produced from the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, when talking about one “gene”, we do not refer to only one sequence. One gene could have different transcription start/termination sites (Soong et al 1994 ), translation start/termination sites (Kochetov et al 2005 ), alternative splicing patterns (Liu et al 2015 ), nucleotide modifications (Chandola et al 2015 ), protein modifications (Fung and Liu 2018 ), and even the switch between coding and non-coding genes, termed domestication (Murray and Murray 2016 ). All these factors and their combinations result in the endless isoforms of transcripts and protein sequences, even they are produced from the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, when talking about one "gene", we do not refer to only one sequence. One gene could have different transcription start/termination sites (Soong et al, 1994), translation start/termination sites (Kochetov et al, 2005), alternative splicing patterns (Liu et al, 2015), nucleotide modifications (Chandola et al, 2015), protein modifications (Fung and Liu, 2018), and even the switch between coding and non-coding genes, termed domestication (Murray and Murray, 2016). All these factors and their combinations result in the endless isoforms of transcripts and protein sequences, even they are produced from the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of an acidic domain in ZFX protein, similar to the activation domain of transcription factors, and a potential nucleic acid-binding domain of 13 "zinc ringers", Palmer et al suggested that ZFX may be a plausible transcription facto (4). L'Haridon et al provided the first demonstration that the ZFX gene encodes a bona fide transcription factor (5). Zinn et al mapped one or more Turner syndrome traits, including short stature, ovarian failure, high-arched palate, and autoimmune thyroid disease in a critical region in Xp11.2-p22.1 (6), implicating the importance of ZFX during game to genes is development and in efficient gametogenesis during adulthood (7).…”
Section: Introductionmentioning
confidence: 99%